Investor response to management decisions : a research-based analysis of actions and effects - Altman, Richard M. (Quorum Books, 1992)
This work concerns management's ability to anticipate how investors will respond to the investing, financing, and operating decisions they make as they manage their business. Claiming that investor behavior is rational and predictable, as supported by extensive research in financial economics, Richard Altman presents a new kind of reference book: the first to bring reasoned theory and the results of exhaustive worldwide academic research to the interpretation of company stock price movements. Following an introductory chapter that provides an overview of the issue, Altman devotes two chapters to examining the investing decisions of management that affect asset, unit, and corporate structures. Investor response to financing decisions and financial policy are covered in the next two chapters, and are followed by a review of the response to operating decisions embodied in management's reported earnings and earnings forecasts. This chapter also looks at investor response to investment research and securities analysis. The market for corporate control and management's defense of that market are analyzed in two subsequent sections, while the link between the managerial labor market and managerial performance, pay, and tenure is also thoroughly explored. Finally, the book concludes with a discussion of management response to investor decisions. This work will be a unique and valuable tool for management professionals and others in the finance, investment, and banking fields. It will also be a useful resource for business students and for public and academic libraries.